Pengaruh Program Tahfidz Al Qur’an Dalam Meningkatkan Kualitas Hafalan Siswa Kelas IV Mi Darul Amanah Kalianda Lampung Selatan - Ulfa Nur Azizah; Arizal Eka Putra; Muhammad Rizkal Fajri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to determine the effect of the Tahfidz Al-Qur'an Program on the Memorization Quality of fourth-grade students at MI Darul Amanah Kalianda. The research employed a quantitative method with causal theory. Hypothesis testing was conducted using the t-test and simple linear regression analysis. Data were collected through questionnaires, observations, and documentation. The study population consisted of 26 fourth-grade students, using a total population approach. Data analysis using SPSS software resulted in the regression equation Y = 31.182 + 0.587X, where the Tahfidz Program significantly influenced Memorization Quality with a significance level of 0.000 (< 0.05). The t-test results showed tcount = 6.927, greater than ttable = 1.711, indicating that the alternative hypothesis (Ha) was accepted. Thus, the Tahfidz Al-Qur'an Program has been proven to have a positive and significant impact on improving students' memorization quality. This study emphasizes the importance of structured tahfidz program implementation, parental support, and student motivation to optimize tahfidz learning outcomes in schools